C-Raf deficiency leads to hearing loss and increased noise susceptibility - de Iriarte Rodríguez, Rocío (Cell Mol Life Sci, 2015)
The family of RAF kinases transduces extracellular information to the nucleus, and their activation is crucial for cellular regulation on many levels, ranging from embryonic development to carcinogenesis. B-RAF and C-RAF modulate neurogenesis and neuritogenesis during chicken inner ear development. C-RAF deficiency in humans is associated with deafness in the rare genetic insulin-like growth factor 1 (IGF-1), Noonan and Leopard syndromes. In this study, we show that RAF kinases are expressed in the developing inner ear and in adult mouse cochlea. A homozygous C-Raf deletion in mice caused profound deafness with no evident cellular aberrations except for a remarkable reduction of the K(+) channel Kir4.1 expression, a trait that suffices as a cause of deafness. To explore the role of C-Raf in cellular protection and repair, heterozygous C-Raf (+/−) mice were exposed to noise. A reduced C-RAF level negatively affected hearing preservation in response to noise through mechanisms involving the activation of JNK and an exacerbated apoptotic response. Taken together, these results strongly support a role for C-RAF in hearing protection. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00018-015-1919-x) contains supplementary material, which is available to authorized users.